Western Christian missions' influence on the public witness of the Nepali Church - Knoetze, Hannes (Missionalia, 2025)
The Nepali Church, with a rich history spanning 70 years, is the fruit of the tireless work of the Nepali Christians who joined the Western Christian missions (WCMs) when they came to Nepal in the 1950s. These partnerships emerged to ‘preach the gospel and build the global church'. However, the WCMs found that they were unable to implement their mission of evangelism and church planting, and instead, became involved in social development. While the WCMs focussed on social works, the Nepali Christians embraced the spiritual aspect of the mission and built the Nepali Church. The divergence in mission objectives between the WCMs and the local Nepali Church led to separate implementation of the integral gospel. This research investigates how this separate mode and objectives of the WCMs and the local Nepali Church influenced the public Christian witness in society. This article highlights the need for a meaningful partnership between the WCMs and the local church. It is an inter- and intra-disciplinary study, attending to the fields of history, development, mission studies, and ecumenical relations.